Locomotion and Topographical Working Memory in Children With Myelomeningocele and Arthrogryposis Multiplex Congenita - Bartonek, Åsa; Guariglia, Cecilia; Piccardi, Laura (Frontiers in Psychiatry, 2021)
Background: In children with myelomeningocele (MMC) and arthrogryposis multiplex congenital (AMC), adequate rehabilitation measures are accessible with the goal of attaining the utmost motor development. However, there is a lack of knowledge as to how children develop navigation utilizing their locomotion abilities. The aim of the present study was to explore topographic working memory in children with MMC and AMC. Methods: For this purpose, we assessed 41 children with MMC and AMC, assigned an ambulation group, and 120 typical developing (TD) children, with mean ages of 11.9, 10.6, and 9.9 years, respectively. All groups performed a topographic working memory test while moving in a walking space and a visuospatial working memory test in a reaching space. Children with MMC and AMC also performed a test to measure their ability to reason on visuospatial material, Raven's Coloured Progressive Matrices. Results: The topographic working memory span was shorter in the MMC group than in the TD group. In general, all ambulation groups had a shorter topographic working memory span than the TD group. The visuospatial working memory span was shorter in the non-ambulation group than in the TD group. Scores from the visuospatial reasoning test were lower in the non-ambulation group than in the community ambulation group. Conclusions: Even though a higher cognitive score was found in the community ambulation group than in the non-ambulation group, topographic working memory was affected similarly in both groups. Including children who develop community ambulation in therapy programs containing aspects of navigation may gain even children with low levels of MMC and AMC. These results evidenced the importance of motor development and navigational experience gained through direct exploration of the environment on topographic memory.